ANALISIS FAKTOR ATAS PENGARUH TIDAK LANGSUNG BRAND NAME DAN KUALITAS KULINER SERTA PENGARUH LANGSUNG KUALITAS KULINER TERHADAP KEPUASAN KONSUMEN - Sugianta - Sugianta (Politeknik Negeri Semarang, 2014)
Object of this article is the culinary industry in Semarang. This article was formulated based on the important fact is found in the field. Where the facts show competition in the culinary industry at this time spawned creativity in formulating the business name of culinary and culinary quality. This is a unique name on one side in an effort to build differentiation to competitors and at the same time aims to influence customer satisfaction. While in the culinary industry it remains an aspect of quality of other important things into superior value. This article attempts to explore further the factors that led to the better culinary value and how the value of culinary and business names into determinants of customer satisfaction. Formulation variables and indicators of the article refer to the previous article. A model has been developed and four hypotheses have been formulated to address the problem of this article. The sampling technique was purposive sampling and quota sampling. Respondents from this article numbered 100 respondents, of which the respondent is a culinary consumer around Semarang State Polytechnic. Data analysis tool used Structural Equation Modeling (SEM) in AMOS 18.0 program. The results of the data analysis this article shows the results of the model and the fourth hypothesis can be accepted article. Managerial implications of providing advice to focus on the indirect effect culinary quality on customer satisfaction around Semarang State Polytechnic through consumer value have the most dominant coefficient.